Aplikasi Mobile untuk Otomatisasi Penerbitan Surat Mahasiswa - Salim Athari; Daru Prasetyawan; Rahmadhan Gatra (Sekawan Institut, 2025)
Effective management of correspondence is a crucial requirement in various organizations to enhance operational efficiency, particularly in supporting lectures in higher education. The issuance of letters for student needs must adhere to specific requirements that must be fulfilled before the letter is issued. This process can sometimes be lengthy as the examination is conducted by officers. The application of information technology enables the acceleration of letter issuance by automating the verification of the necessary requirements. The use of mobile technology also facilitates flexible access for users at any time and from any location. Mobile applications are designed to address user needs in terms of functionality, ease of use, and optimal performance. This study aims to develop a mobile-based automatic letter system that assists students in obtaining letters required during lectures. The application operates automatically, meaning that the fulfillment of the requirements necessary for issuing letters can occur without the intervention of officers to verify them. The development of this system follows the Software Development Life Cycle (SDLC), which encompasses needs analysis, design, implementation, and system testing. Application development incorporates data obtained from other existing systems such as academic information systems, personnel information systems, and electronic official manuscript systems. This application utilizes the Application Programming Interface (API) to communicate with other applications. The development of this system employs the Dart programming language and the Flutter framework. From the results of User Acceptance Testing (UAT), a score of 93.19% was achieved, indicating that the application was well received by users.